Melatonin in Pain Modulation: Analgesic or Proalgesic? - Liu, Yongliang; He, Hongwen; Huang, Fang (Scientific Research, 2014)
Melatonin, as an endogenous hormone produced mainly in the pineal gland in a clear circadian fashion, has diverse physiological functions, such as the control of circadian rhythms, sleep regulation, antioxidant, etc. Recently, accumulating researches about melatonin and pain have been reported. In this review, comparison and summary about analgesic/proalgesic effect of melatonin in inflammatory and neuropathic pain will be made. Some possible pathways of melatonin involved in dual pain modulation might help to explain all these conflicting results in various situations.
Keywords: Melatonin; Pain; Modulation; Analgesic; Pro-Algesic